Epithelial–Myoepithelial Carcinoma of the Esophagus: A Case Report - Wu, Haohao; Zhang, Fangbiao; Peng, Jiahui; Wu, Zhiju; Zhang, Xiangyan; Wu, Xingzhen (Frontiers in Surgery, 2022)
Epithelial–myoepithelial carcinoma (EMC) of the esophagus is a rare biphasic tumor with low malignant potential, which has not previously been reported in the published literature. The present study describes the case of an asymptomatic, 53-year-old male who presented with EMC in the esophagus during a gastroscopic examination. Esophageal computed tomography (CT) showed thickening of the wall of the lower esophagus with a thickness of about 0.7 cm, and an enhanced scan showed uneven enhancement of the thickened esophageal wall. Thoracoscopic esophagectomy was performed because the tumor was malignant. Histopathology revealed that the tumor was characterized by a biphasic architecture consisting of cuboidal ductal cells and myoepithelial cells. The patient’s postoperative recovery was eventful, an anastomotic fistula occurred, and the patient was discharged from the hospital after 84 days. One year postsurgery, the patient remained in good health, with no evidence of metastasis and recurrence.